On Council of Europe action in the field of sports: analysis of the European Convention on the Manipulation of Sports Competitions - Pérez González, Carmen (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
This work aims to analyze the international measures adopted to fight against corruption in sports and, in particular, the European Convention on the manipulation of sports competitions, recently adopted by the member States of the Council of Europe. It is well known that this international organization has developed an important activity in the realm of sport. The adoption of the European Convention against doping (1989), the European Convention on spectator violence and misbehavior at sports events and in particular at football matches (1985) and an important number of resolutions of the Committee of Ministers and the Parliamentary Assembly have to be mentioned in this sense. By doing so, the Council of Europe has decisively contributed to the emergence of International Sports Law, which can be identified as a new area of International Law.
Keywords: international sports law; council of europe; fight against sports corruption; manipulation of sports competitions; cooperation with sports bodies